Metal nanoparticles in diesel exhaust derived by in-cylinder melting of detached engine fragments. (January 2015) - Liati, Anthi; Pandurangi, Sushant Sunil; Boulouchos, Konstantinos; Schreiber, Daniel; Arroyo Rojas Dasilva, Yadira
Abstract: A wide range of environmental and health effects are linked to combustion-generated pollutants related to traffic. Nanoparticles, in particular, are a major concern for humans since they can be inhaled and have potentially toxic effects. The variability and sources of combustion-related nanoparticle pollutants remain inadequately investigated. Here we report the presence of ca. 5–100 nm large Fe3 O4 nanoparticles, in form of agglomerates, in diesel exhaust. The mode of occurrence of these nanoparticles, in combination with their chemical composition matching that of steel indicate that they derive by melting of engine fragments in the combustion chamber and subsequent crystallization during cooling. To evaluate this hypothesis, we applied CFD simulations of material transport in the cylinder of a diesel engine, assuming detachment of steel fragments from various sites of the cylinder. The CFD results show that fragments ≤20 μm in size dislodged from the piston surface or from the fuel nozzle interior can be indeed transported to such hot areas of the combustion chamber where they can melt. The simulation results concur with the experimental observations and point out that metal nanoparticle formation by in-cylinder melting of engine fragments can occur in diesel engines. The present study proposes a hitherto neglected formation mechanism of metal nanoparticle emissions from internal combustion engines raising possible environmental and health concerns, especially in urban areas. Highlights: Traffic-related metal nanoparticle emissions can pose environmental and health concerns. Fe3 O4 nanoparticle agglomerates occur in diesel exhaust. Steel fragments detached from cylinder engine parts can melt in the combustion chamber. A hitherto neglected mechanism of metal nanoparticle formation from internal combustion engines is suggested.